Diabetes and Insulin Therapy, but Not Metformin, Are Related to Hepatocellular Cancer Risk - Luca Miele; Cristina Bosetti; Federica Turati; Gianlodovico Rapaccini; Antonio Gasbarrini; Carlo La Vecchia; Stefania Boccia; Antonio Grieco (Gastroenterology Research and Practice)
Introduction. Metabolic conditions, including type 2 diabetes, have been related to hepatocellular carcinoma (HCC) risk. We have further analyzed the role of diabetes and antidiabetic treatments on HCC. Methods. Data derived from a hospital-based case-control study (Italy, 2005–2012) on 224 HCC patients and 389 controls. Odds ratios (ORs) were estimated using multiple logistic regression models. Results. Sixty-nine (30.9%) cases versus 52 (13.5%) controls reported a diabetes diagnosis, corresponding to a multivariate OR of 2.25 (95% confidence interval, CI = 1.42–3.56). A stronger excess risk emerged for a longer time since diabetes diagnosis (OR = 2.96 for <10 years and 5.33 for ≥10 years). Oral therapies were inversely, though not significantly, related to HCC risk, OR being 0.44 for metformin and 0.88 for sulfonylureas; conversely, insulin was nonsignificantly directly associated (OR = 1.90). Compared to nondiabetic subjects who were never smokers, those who were diabetics and ever smokers had an OR of 6.61 (95% CI 3.31–13.25). Conclusion. Our study confirms an over 2-fold excess HCC risk in diabetics, with a stronger excess risk in diabetic subjects who are also tobacco smokers. Metformin may decrease the risk of HCC, whereas insulin may increase the risk.